Current Understanding of BRAF Alterations in Diagnosis, Prognosis, and Therapeutic Targeting in Pediatric Low-Grade Gliomas - Penman, Catherine Louise; Faulkner, Claire; Lowis, Stephen P.; Kurian, Kathreena M. (Frontiers in Oncology, 2015)
The mitogen-activated protein kinase (MAPK) pathway is known to play a key role in the initiation and maintenance of many tumors as well as normal development. This often occurs through mutation of the genes encoding RAS and RAF proteins which are involved in signal transduction in this pathway. BRAF is one of three RAF kinases which act as downstream effectors of growth factor signaling leading to cell cycle progression, proliferation, and survival. Initially reported as a point mutation (V600E) in the majority of metastatic melanomas, other alterations in the BRAF gene have now been reported in a variety of human cancers including papillary thyroid cancer, colon carcinomas, hairy cell leukemia, and more recently in gliomas. The identification of oncogenic mutations in the BRAF gene have led to a revolution in the treatment of metastatic melanoma using targeted molecular therapies that affect the MAPK pathway either directly through BRAF inhibition or downstream through inhibition of MEK. This review describes the molecular biology of BRAF in the context of pediatric low-grade gliomas, the role of BRAF as a diagnostic marker, the prognostic implications of BRAF, and evidence for therapeutic targeting of BRAF.